Characterization and catalytic reactivity of mordenite – Investigation of selective oxidation of benzyl alcohol. (29th March 2015) - Narayanan, S.; Vijaya, J. Judith; Sivasanker, S.; Alam, Mahboob; Tamizhdurai, P.; Kennedy, L. John
Graphical abstract: The HR-SEM images of the commercial and dealuminated zeolite (66MOR(AT-3.0)) are shown in the figure. Compared with commercial zeolite, a significant transformation was observed in the morphology and particle size of the dealuminated mordenite zeolite. Also, the dealuminated mordenite samples appeared as less agglomerated, with less densely packed crystallites, than their corresponding commercial ones. The commercial mordenite sample particle size is between 300 and 400 nm. However, the observed particle size of the dealuminated mordenite (66MOR(AT-3.0)) is in the range 100–300 nm only. Abstract: Commercial mordenite was dealuminated with hydrochloric acid by refluxing at 373 K for different durations to develop a stable catalyst for the selective oxidation of benzyl alcohol. The commercial and dealuminated mordenite samples were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), Fourier transform infrared (FTIR) spectroscopy, N2 adsorption–desorption, high resolution scanning electron microscopy (HR-SEM) and temperature programmed desorption (NH3 -TPD). The results revealed that the external surface area increased with acid treatment while preserving the mordenite structure. The catalytic performance of acid-treated mordenite was evaluated in the selective oxidation of benzyl alcohol with tert -butyl hydroperoxide (TBHP) as the oxidant and acetonitrile as the solvent. The influences of the variation in catalyst amount, reaction temperature, TBHP/BzOH ratio and SiO2 /Al2 O3 ratio (SAR) were investigated. The sample with a SAR of 33, obtained after acid treatment for 3 h, exhibited a higher conversion than the other samples. At the optimum conditions, the benzyl alcohol conversion and benzaldehyde selectivity were about 99% and 98%, respectively, over this sample. This catalyst could be reused at least four times without any significant loss in its activity and selectivity. The selective oxidation of substituted benzyl alcohols is also reported.